1997
DOI: 10.1046/j.1365-3040.1997.d01-51.x
|View full text |Cite
|
Sign up to set email alerts
|

Directed overexpression of PHYA locally suppresses stem elongation and leaf senescence responses to far‐red radiation

Abstract: Ectopic overexpression of an oat PHYA cDNA in tobacco under the cauliflower mosaic virus 35S promoter results in plants with reduced morphological responses to far-red radiation (FR). We have tested the hypothesis that it is possible to molecularly 'mask' stems and leaves to FR-induced elongation and senescence responses by targeting the overexpression ol'PHYA with appropriate promoters. Oat PHYA was expressed in tobacco {Nicotiana tahacum L. cv Xanthi) under the 35S and two Arabidopsis promoters: UBQl and CAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
41
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 36 publications
5
41
2
Order By: Relevance
“…Red light has long been considered to be a key negative signal for plant senescence, because pulses of red light substantially delay dark-induced senescence (DIS) in a few plant species, supposedly via phytochromes 24 and a low ratio of red/far-red light causes senescence in tobacco leaves 25 . Red light activates and far-red light inactivates phytochromes; darkness also causes slow inactivation of phytochromes 23 .…”
mentioning
confidence: 99%
“…Red light has long been considered to be a key negative signal for plant senescence, because pulses of red light substantially delay dark-induced senescence (DIS) in a few plant species, supposedly via phytochromes 24 and a low ratio of red/far-red light causes senescence in tobacco leaves 25 . Red light activates and far-red light inactivates phytochromes; darkness also causes slow inactivation of phytochromes 23 .…”
mentioning
confidence: 99%
“…The most visible effect of senescence is Chl degradation. For instance, illumination of tobacco (Nicotiana tabacum) leaves with far red causes a drop in Chl content, which does not occur in Nicotiana plants overexpressing oat (Avena sativa) phyA (Rousseaux et al, 1997). We have observed that the levels of mRNA of two enzymes involved in Chl catabolism in Arabidopsis, products of the AtCLH1 and AtCLH2 genes, dramatically increase (by almost two and one order of magnitude, respectively) upon illumination with white light.…”
mentioning
confidence: 84%
“…It was shown that leaves of soybean (Guiamet et al, 1989) and sunflower (Rousseaux et al, 1996) senesced more quickly when the red:far-red ratio of the light they received was decreased, and that far-red light induces chlorophyll loss in tobacco leaves (Rousseaux et al, 1997). It also has been shown that tobacco and overexpressing oat phytochrome A display both delayed leaf senescence (Cherry et al, 1991) and an inhibited response to the senescence promoting effects of far-red light (Rousseaux et al, 1997).…”
Section: Wwwintechopencommentioning
confidence: 99%
“…It also has been shown that tobacco and overexpressing oat phytochrome A display both delayed leaf senescence (Cherry et al, 1991) and an inhibited response to the senescence promoting effects of far-red light (Rousseaux et al, 1997). Weaver and Amasino (2001) examined a hy2/hy3 phytochrome double mutant line, in which there is no phytochrome B and low levels of all other phytochromes (Parks and Quail, 1991;Somers et al, 1991), and observed it to behave much like wild-type controls, after both whole-plant and individual leaf dark treatments.…”
Section: Wwwintechopencommentioning
confidence: 99%